Information technology in disaster risk reduction : third IFIP TC 5 DCITDRR International Conference, ITDRR 2018, held at the 24th IFIP World Computer Congress, WCC 2018, Poznan, Poland, September 20-21, 2018, Revised Selected Papers /: third IFIP TC 5 DCITDRR International Conference, ITDRR 2018, held at the 24th IFIP World Computer Congress, WCC 2018, Poznan, Poland, September 20-21, 2018, Revised Selected Papers. (2019) - Unknown
No abstract available